2018
DOI: 10.3390/ma11122540
|View full text |Cite
|
Sign up to set email alerts
|

Hydrostatic High-Pressure Post-Processing of Specimens Fabricated by DLP, SLA, and FDM: An Alternative for the Sterilization of Polymer-Based Biomedical Devices

Abstract: In this work, we assess the effects of sterilization in materials manufactured using additive manufacturing by employing a sterilization technique used in the food industry. To estimate the feasibility of the hydrostatic high-pressure (HHP) sterilization of biomedical devices, we have evaluated the mechanical properties of specimens produced by commercial 3D printers. Evaluations of the potential advantages and drawbacks of Fused Deposition Modeling (FDM), Digital Light Processing (DLP) technology, and Stereol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Compared with traditional SLA technology, DLP technology can cure the entire pattern in a layer in a single exposure, thereby improving efficiency ( Figure 5 ) [ 69 , 70 , 71 ]. Zhao et al used the DLP method to print environment-responsive self-folding origami structures based on polyethylene glycol diacrylate (PEGDA) [ 72 ].…”
Section: Additive Manufacturing (Am) Technologies For Four-dimensimentioning
confidence: 99%
“…Compared with traditional SLA technology, DLP technology can cure the entire pattern in a layer in a single exposure, thereby improving efficiency ( Figure 5 ) [ 69 , 70 , 71 ]. Zhao et al used the DLP method to print environment-responsive self-folding origami structures based on polyethylene glycol diacrylate (PEGDA) [ 72 ].…”
Section: Additive Manufacturing (Am) Technologies For Four-dimensimentioning
confidence: 99%
“…Because the projection of a digital image enables the entire pattern of each layer to be cured in one exposure, the printing and production speed of the DLP process is much faster than the conventional SLA technique. [ 69 ] Zhao et al printed poly(ethylene glycol)diacrylate (PEGDA)‐based, environmentally responsive self‐folding origami structures using DLP methods. [ 70 ] By controlling the light intensity, the degree of crosslinking within the thin sheet of polymer was different, resulting in shape bending when the uncured oligomers were desolvated from the network.…”
Section: Additive Manufacturing Technologies For 4d Printingmentioning
confidence: 99%
“…Therefore, EtO would be the most effective sterilization method 162 . Finally, regarding SLA, in Robles et al 89 hydrostatic pressure (HHP) showed more potential to be used in SLA than autoclave for SLA printed materials.…”
Section: Visualization For Preoperative Surgical Planningmentioning
confidence: 99%